2017
DOI: 10.1016/j.cedpsych.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Professional development of teachers in the implementation of a strategy-focused writing intervention program for elementary students

Abstract: In this study we examined the effectiveness of Tekster [Texter], a comprehensive program for writing for the upper elementary grades, combining strategy instruction, text structure instruction, and the teaching of self-regulation skills with observational learning, explicit instruction, and (guided) practice to address both the focus of instruction (what is taught) and the mode of instruction (how it is taught). Further, we investigated the added value of a professional development program for teachers on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…First, variability in ratings of lesson quality indicates that a specific focus on the informational text genre might be just as important for teachers as for students, particularly with regard to strategy instruction. Research in text structure and text feature training for inservice teachers has been promising (Brugar & Roberts, 2017; Koster, Bouwer, & van den Bergh, 2017), likely because of the specific, job‐embedded content focus of this type of professional development (Penuel, Fishman, Yamaguchi, & Gallagher, 2007). Elements of ambitious instruction with informational text should also be considered for more in‐depth inclusion in preservice preparation experiences.…”
Section: Discussionmentioning
confidence: 99%
“…First, variability in ratings of lesson quality indicates that a specific focus on the informational text genre might be just as important for teachers as for students, particularly with regard to strategy instruction. Research in text structure and text feature training for inservice teachers has been promising (Brugar & Roberts, 2017; Koster, Bouwer, & van den Bergh, 2017), likely because of the specific, job‐embedded content focus of this type of professional development (Penuel, Fishman, Yamaguchi, & Gallagher, 2007). Elements of ambitious instruction with informational text should also be considered for more in‐depth inclusion in preservice preparation experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is in line with the results obtained by Ismail (2011) who reported that students had positive views about writing and demonstrated awareness of their writing needs and requirements. Thus, lack of suitable teaching materials and essential knowledge for teaching writing skills effectively are considered to be reasons that go beyond the shortcomings of language student teachers (Koster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Koster, Bouwer, and Bergh (2017) write that, in the Netherlands and many other countries, concerns have been raised about the writing proficiency of language student teachers in terms of teaching students to ''[be] able to write coherent texts, with a simple linear structure on various familiar topics; the text includes an introduction, body, and ending" (p.1). Koster et al (2017) specified two reasons for the shortcomings of language student teachers: (1) lack of suitable teaching materials, and (2) lack of the necessary skills and knowledge to teach writing effectively (p.2). Teacher educators in preparation programmes often do not explain how student teachers should approach a writing task, discuss it, and provide constructive feedback.…”
mentioning
confidence: 99%
“…The third design team made peer modeling video clips that were used as part of Tekster instruction. After the writing tasks and video clips were created, the authors wrote the detailed lesson plans for each grade level and subsequently piloted the program (see Koster, Bouwer, & Van den Bergh, 2016).…”
Section: Methodsmentioning
confidence: 99%